Isolation of Stigmasterol and ?-Sitosterol from the dichloromethane extract of Rubus suavissimus (International Current Pharmaceutical Journal, 2012)
Purification of the dichloromethane (CH2Cl2) fraction of the aqueous extract of Rubus suavissimus resulted in the isolation of two sterols namely stigmasterol and ?-sitosterol. The structures of the isolated compounds were characterized on the basis of extensive spectral data (1D and 2D NMR; and MS) and in comparison with their literature data.DOI: http://dx.doi.org/10.3329/icpj.v1i9.11613 International Current Pharmaceutical Journal 2012, 1(9): 239-242